1982
DOI: 10.1073/pnas.79.3.927
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the selective toxicity of alloxan to the pancreatic B cell.

Abstract: The diabetogenic agent alloxan exerts a preferential cytotoxic effect on the pancreatic B cell. The determinants of such a tissue specificity were investigated. Alloxan accumulated rapidly in liver and pancreatic islets but much more slowly in muscle. The activity of glutathione peroxidase and the resistance to exogenous peroxide were -20 times higher in liver and kidney than in islets, intermediate values being found in exocrine pancreas and muscle. These findings suggest that the selective cytotoxicity of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
143
0
3

Year Published

1984
1984
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(151 citation statements)
references
References 24 publications
5
143
0
3
Order By: Relevance
“…Alloxan and streptozotocin cause a selective destruction of insulin-producing cells by overproduction of reactive oxygen and nitrogen intermediates [51,52,63]. Up to now there are no data on their influence on peroxiredoxin expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alloxan and streptozotocin cause a selective destruction of insulin-producing cells by overproduction of reactive oxygen and nitrogen intermediates [51,52,63]. Up to now there are no data on their influence on peroxiredoxin expression.…”
Section: Discussionmentioning
confidence: 99%
“…The beta cell toxin alloxan is used to generate animal models of Type I diabetes mellitus. The substance is able to destroy insulin-producing beta cells by generating oxygen radicals [51]. We investigated the effect of alloxan on Prxs expression in INS-1 cells using semiquantitative RT-PCR and western blot analysis.…”
Section: Up-regulation Of Prx I and Ii Expression By Allox-mentioning
confidence: 99%
“…Stimulation of oxygen free radical production in pancreatic islet cells, however, might be expected to have lethal consequences to islet cells since islet cells possess very low free radical scavenging enzyme activities [19,20], and therefore are exquisitely vulnerable to free radical-induced injury [20]. Cytokine-induced oxygen free radicals are primarily products of arachidonic acid metabolism in many cell types, and we have recently observed that inhibitors of arachidonic acid metabolism can protect islet cells from the cytotoxic effects of TNF and IFN-y.…”
Section: Free Radical Scavengers Protect Against Cytokinesmentioning
confidence: 99%
“…Such a mechanism for cytokinemediated islet cell injury was first suggested by Mandrup-Poulsen et al [18], and is based on the observations that islet cells possess very low oxygen free radical scavenging enzyme activities [19,20], and are exquisitely vulnerable to free radicals [20]. In the present report, we demonstrate that the oxygen free radical scavengers, dimethylthiourea and citiolone, can significantly protect islet cell monolayer cultures from lysis by the oxygen free radical generators, t-butylhydroperoxide and alloxan, as well as by toxic combinations of the cytokines, IL-1, TNF, and IFN-y..…”
mentioning
confidence: 99%
“…Also, there is an uptake of alloxan in liver mitochondria both in vivo and in vitro [17], and our preceding work has demonstrated that alloxan affects ion transport in isolated liver mitochondria [18,19]. Recent studies by others, not specifically directed to mitochondria, have verified a considerable, rapid accumulation [20] and cytotoxicity [21] of alloxan in hepatocytes. However, mitochondria from mouse endocrine pancreas can be isolated [17], and, to facilitate the interpretation of the data with regard to diabetogenicity of alloxan, some additional experiments were carried out on mitochondria from the endocrine pancreas.…”
mentioning
confidence: 95%